Antagonism Potentials of Endophytic Fungi from Lemongrass (Cymbopogon nardus (L.) Rendle) on Escherichia coli - Al Hadi, Salma Khatami; Narulita, Erlia; Murdiyah, Siti (Jurnal ILMU DASAR, 2022)
This study aimed to determine the potential antagonism performed by the endophytic fungi of lemongrass against Escherichia coli. Five species of endophytic fungi were tested using agar well method. These fungi consist of Paecilomyces lilacinus, Penicillium sp., Trichoderma viride, Fusarium oxysporum, and Fusarium sp., each was taken from roots, stem, and leaves, respectively. Chloramphenicol and aquadest were used as control. The results showed that there is significant inhibition of E. coli compared to the negative control. Paecilomyces lilacinus showing the most prominent inhibition with 74.67%, followed by unknown species of Fusarium 47.33%, Penicillium sp 42.67%, Fusarium oxysporum 21.67%, and Trichoderma viride 17.43%. It can be concluded that all five isolates of endophytic fungi from lemongrass (Cymbophogon nardus (L.) Rendle) have the ability to inhibit the growth of E. coli, and thus have antagonism potential against E. coli.